Species richness and turnover patterns for tropical and temperate plants on the elevation gradient of the eastern Himalayan Mountains - Thorne, James H.; Choe, Hyeyeong; Dorji, Lobzang; Yangden, Kezang; Wangdi, Dorji; Phuntsho, Younten; Beardsley, Karen (Frontiers in Ecology and Evolution, 2022)
Understanding species’ elevational distributions in mountain ecosystems is needed under climate change, but remote biodiverse mountain areas may be poorly documented. National Forest Inventories (NFIs) offer a potential source of data. We used NFI records from Bhutan to ask three questions about elevational richness patterns of Himalayan woody plant species. First, does the mean elevation for all species differ from those species whose entire elevational distribution is recorded in the survey? Second, how does the elevation of maximum richness differ when combining species originating from temperate and tropical regions vs analyzing them separately? And third, do the highest species turnover rates adjoin elevation zones of maximum species richness? We used 32,198 species records from 1685 forest plots along a 7522 m gradient to map species elevation ranges. Species whose entire range was documented were those whose lowest records located above 400 m, while bare rock defined all species’ upper limits. We calculated species richness and turnover using 400 m elevation bands. Of 569 species, 79% of temperate and 61% of tropical species’ elevation ranges were fully sampled within the NFI data. Mean elevation of tree and shrub species differed significantly for temperate and tropical species. Maximum combined species richness is from 1300-1700 m (277 species), differing significantly from maximum tropical (900-1300 m, 169) and temperate species (2500-2900 m, 92). Temperate tree turnover rate was highest in the bands adjoining its maximum species richness (2500-2900 m). But turnover for tropical trees was highest several bands above maximum species richness, where turnover and decrease in richness interact. Shrub species turnover patterns similar, but rates were generally higher than for trees. Bhutan’s NFI records show that woody plant species are arrayed on the Himalaya in part according to floristic origins, and that combining temperate- and tropical-originating floras for gradient-based studies such as species richness and turnover obscures actual elevational patterns. In addition, species whose ranges extend below the Himalayan elevation gradient should be accounted for in future studies that correlate climate and environment factors with elevational species richness patterns.